Diseño de una línea de producción para el ambiente de trabajo simulado del laboratorio de producción industrial de la Universidad de las Américas - Zambrano Arias, Juan Pablo Trajano (2018)
The objective of this work was to design a simulated work environment for the UNIVERSITY OF THE AMERICAS (UDLA) specifically will be located next to the laboratories of the engineering career in Industrial Production, the objective is to implement the design of a simulated work environment. which will provide practical training and can be implemented: manufacturing processes, lean tools, etc., by means of a mock-up of a real-size assembly line with simulated vehicles constructed of wood or steel, to provide the student with the different scenarios of real-world manufacturing, reproducing exactly different activities such as inventory control, line balancing, quality control, process management, etc. Through a brief historical review of the productive system and its evolution over the years, the different manufacturing processes, method engineering, the different types of plant distribution and the importance of measuring work activities are described. different phases necessary for the design and construction of a prototype, the direct and indirect costs, the analysis of unit wrecks of the built prototype and detailing the construction and assembly process to manufacture the Jeep type vehicle prototype. Once the prototype has been designed to be assembled, the simulated work environment is designed, which consists of the design of the plant with its assembly line, assembly processes, taking of time, plant equipment and the design of the factory that for the present project a barn was designed taking into account the structural analysis of the foundation and the metallic structure.